USE OF DENOSUMAB IN GIANT-CELL TUMOR AT A PUBLIC HOSPITAL IN SOUTHERN BRAZIL: REPORT OF 13 CASES - Tamise da Silva Baptista; Lucilda Cerqueira Lima; Aline Rocha Lino; Gerson Gandhi Ganev; Paulo Kechele; Rita Ferrúa Farias de Oliveira (Brazilian Journal of Oncology)
Giant-cell tumor is a relatively rare neoplasia, benign but locally aggressive, that causes significant bone destruction with predilection for epiphyseal and metaphyseal regions of long bones and the spine. Definitive treatment is surgical, with complete tumoral resection followed by autograft, homograft, arthrodesis, unconventional endoprostheses or methylmethacrylate. In most cases, surgery is accompanied by high morbidity and variable recurrence rates, depending on the site, size and type of surgical intervention.Denosumab, a RANKL inhibitor, acts by decreasing tumoral osteoclastic activity and is approved by the Food and Drug Administration for treatment of GCT when surgery is not possible or when it is associated with high morbidity. This report of cases is based on the review of medical records from the Ambulatory Service for Adolescents and Young Adults (AYA), aiming to show the experience of the Service with the use of denosumab for neoadjuvant purposes.